Facile low temperature processed nanostructure ZnO QD based thin films for potential perovskite solar cell: thickness dependence of crystal and electrical properties. Issue 1 (1st December 2022) - Muhammad, S; Nomaan, A T; Olaoye, A O; Bello, M; Zyoud, S H; Idris, M I; Rashid, M
Abstract: The precipitation-spin coating technique is employed to prepare nanostructure ZnO quantum dot (QD) films at different thicknesses. The X-ray diffraction analysis reveals the polycrystalline thin film growth along (101) plane and crystallinity improvement with thickness rise. The increase in thickness causes an increase (5.14 - 7.73 nm) and a decrease (3.39- 3.22 eV) in grain size and bandgap respectively. At optimized thickness, the ZnO QD thin film exhibits 72 % transmittance with the lowest resistivity of 16.24 x 10 -2 Ωcm and highest carrier mobility of 15.38 cm 2 /Vs rendering it viable for potential utilization as an electron transport layer for perovskite devices.